Public health impact of pneumococcal conjugate vaccination: a review of measurement challenges. (3rd October 2021) - Horn, Emily K; Wasserman, Matt D; Hall-Murray, Cassandra; Sings, Heather L; Chapman, Ruth; Farkouh, Raymond A
ABSTRACT: Introduction: Modeling analyses have attempted to quantify the global impact of pneumococcal conjugate vaccines (PCVs) on pneumococcal disease (PD), however these pediatric models face several challenges in obtaining comprehensive impact measurements. Areas Covered: We present several measurement challenges and discuss examples from recently published pediatric modeling evaluations. Challenges include estimating the number of infants fully or partially vaccinated with PCVs, inclusion of indirect effects of vaccination, accounting for various dosing schedules, capturing effect of PCVs on nonspecific, noninvasive PD, and inclusion of adult PCV use. Expert Opinion: The true impact of PCVs has been consistently underestimated in published analyses due to multiple measurement challenges. Nearly 100 million adults are estimated to have received PCV13 over the last decade globally, potentially preventing up to 662 thousand cases of PD. Approximately 4.1 million cases of invasive PD alone may have been averted through indirect protection. Estimates of PCV impact on noninvasive PD remain a challenge due to altered epidemiology. Program switches, incomplete vaccination, and private market uptake among children also confound PD impact estimates. Taken together, the number of averted PD cases from PCV use in the last ten years may be up to three times higher than estimated in previous studies.